2016
DOI: 10.1039/c6nr04239b
|View full text |Cite
|
Sign up to set email alerts
|

Chemically-doped graphene with improved surface plasmon characteristics: an optical near-field study

Abstract: One of the most fascinating and important merits of graphene plasmonics is their tunability over a wide range. While chemical doping has proven to be a facile and effective way to create graphene plasmons, most of the previous studies focused on the macroscopic behaviors of the plasmons in chemically-doped graphene and little was known about their nanoscale responses and related mechanisms. Here, to the best of our knowledge, we present the first experimental near-field optical study on chemically-doped graphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 64 publications
(74 reference statements)
0
17
0
Order By: Relevance
“…Therefore, one can manipulate the plasmonics in the graphene by charge carrier-doping approaches, such as electrostatic gating or chemical doping. Our previous study revealed that the graphene plasmon strengths and wavelengths were enhanced by HNO 3 doping, which was due to the injection of free holes and the reduction of the plasmon damping rates 39 .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, one can manipulate the plasmonics in the graphene by charge carrier-doping approaches, such as electrostatic gating or chemical doping. Our previous study revealed that the graphene plasmon strengths and wavelengths were enhanced by HNO 3 doping, which was due to the injection of free holes and the reduction of the plasmon damping rates 39 .…”
Section: Resultsmentioning
confidence: 97%
“…For the disk with L =90 nm, the electromagnetic field was tightly confined to a bright spot ( Figure 6c ). These behaviors originated from the increase of the graphene plasmon wavelengths upon hole injections 39 , whereby the interference nodes within a specific graphene disk are reduced. The dependence of the interference patterns on chemical doping suggests that one can tailor the electromagnetic fields of the graphene nanostructure with chemical doping without modifying the geometry.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in our previous study, this can introduce slight hole-doping to the pristine graphene flake. [9] Specifically, according to the relation…”
Section: Resultsmentioning
confidence: 99%
“…Obviously, as the carrier concentration increases, the plasmon amplitude increases correspondingly, which is consistent with previous results. [9,10] Furthermore, the plasmon amplitude of the zigzag edge upon chemical doping is stronger than that of the doped www.advopticalmat.de armchair edge. Another interesting issue is that it is known that the electron-phonon interactions will be stronger at the armchair edge, [33] which can impact the 1D edge plasmon behaviors therein.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation